Algoritma Fisher-Yates Shuffle dan Flood Fill sebagai Maze Generator pada Game Labirin - D.J. Owen Hoetama; Farica Perdana Putri; P.M. Winarno (Ultima Computing : Jurnal Sistem Komputer, 2018)
Maze game is an interesting game and used to spend time. However, in the maze game, the level used forthis game still uses static levels. Static levels make the maze shape stay the same if we play the same level. Thus, players will quickly feel bored because it finds the same complexity. Maze generator is a static level problem solution on the maze game. This research uses Fisher-Yates Shuffle algorithm and Flood Fill algorithm to make maze generator. Fisher-Yates Shuffle algorithm is used for wall position randomization and Flood Fill algorithm to keep the maze results to remain resolved. The results of the application implementation yielded 30 mazes and were tested using the Hamming Distance algorithm, yielding that the result of the maze formed is always different. The average percentage rate difference produced 48% each time the maze was formed. The results of the maze that was formed performed perfect maze checking with the result of 83.33% percentage. Index Terms— Fisher-Yates Shuffle, Flood Fill, MazeGenerator, Hamming Distance